تقنية الإيضاح لترجمة معاني القرآن الكريم الآيات القرآنية المختارة المترجمة إلى الإنجليزية لــــ"هلالي" و"خان" أنموذجاً (دراسة تحليلية وتطبيقية في ضوء استراتيجية الترجمة بالإيضاح لـ " منى بيكر") - Dr. Muhammad Nawaz; Dr. Naseem Mahmood (jihat-ul-islam, 2022)
It is recognized that translation is termed as a source of communication, and a tool for transferring the intended message to others. Translation techniques contribute to achieve equivalence between source text and target text through finding out equivalent words aiming at transferring the message of the author of the source text to the reader of the target text. Translation of any religious text like the text of the Holy Qur’an is a huge challenge as it has sensitive text consisting of numerous devices based on rhetorical, stylistic, linguistic and semantic expression. For coping with such type of enormous challenge of rendering the meanings of the Holy Qur’an focusing on the intended meanings and message of the Holy Qur’an, various strategies and techniques are adopted by translators including the translation technique termed by Mona Baker as “Translation by illustration”, and termed it as “Explicitation” by other scholars like Vinay and Darbelnet, and Shoshana Blum kulka. This study investigates the role of translation technique titled “Translation by illustration” in transferring the meaning of the Holy Qur’an to English speaking readers by focusing on some selected Qur’anic verses translated by Hilali and Khan into English. It also analyses that to what extent the divine message of Allah Almighty was transferred faithfully and accurately to the English readers through adaptation of the translation technique by illustration. At the end some findings and recommendations have been mentioned to highlight the importance of translation technique by illustration for transferring the sensitive meanings with their all types of styles and expressions based on rhetoric, semantic and cultural features to others.